Pengaruh Islamic Branding dan Brand Image terhadap Keputusan Pembelian dengan Trust sebagai Variabel Intervening pada Pengguna Skincare Wardah di Kota Semarang - Arfina Shaharani; Lutfi Nurcholis (ARZUSIN, 2026)
The growth of the halal cosmetics industry in Indonesia has intensified competition among brands, particularly in skincare products, thereby necessitating value-based marketing strategies that can build consumer trust. Wardah, as a pioneer of halal cosmetics, employs Islamic branding and brand image to strengthen trust and encourage consumers’ buying decisions. This study aims to analyze the influence of Islamic branding and brand image on buying decisions with trust as an intervening variable among Wardah skincare users in Semarang City. The research used a quantitative approach with an explanatory research design. Data were collected through questionnaires administered to Wardah skincare users using purposive sampling and were analyzed using the Partial Least Square (PLS) method with the SmartPLS application. The results show that Islamic branding and brand image have a positive and significant effect on trust. Furthermore, trust has a positive and significant effect on buying decisions and is proven to mediate the influence of Islamic branding and brand image on purchase decisions. These findings affirm that the consistent application of Islamic values and the strengthening of brand image can enhance consumer trust and drive purchase decisions for Wardah skincare products. The implications of this study highlight the importance of value- and trust-based marketing strategies in strengthening the competitiveness of halal cosmetics brands amid increasingly intense industry competition.